Methods for high throughput validation of amplified fragment pools of BAC DNA for constructing high resolution CGH arrays - Watson, Spencer K (BioMed Central, 2004)
BACKGROUND: The recent development of array based comparative genomic hybridization (CGH) technology provides improved resolution for detection of genomic DNA copy number alterations. In array CGH, generating spotting solution is a multi-step process where bacterial artificial chromosome (BAC) clones are converted to replenishable PCR amplified fragments pools (AFP) for use as spotting solution in a microarray format on glass substrate. With completion of the human and mouse genome sequencing, large BAC clone sets providing complete genome coverage are available for construction of whole genome BAC arrays. Currently, Southern hybridization, fluorescent in-situ hybridization (FISH), and BAC end sequencing methods are commonly used to identify the initial BAC clone but not the end product used for spotting arrays. The AFP sequencing technique described in this study is a novel method designed to verify the identity of array spotting solution in a high throughput manner. RESULTS: We show here that Southern hybridization, FISH, and AFP sequencing can be used to verify the identity of final spotting solutions using less than 10% of the AFP product. Single pass AFP sequencing identified over half of the 960 AFPs analyzed. Moreover, using two vector primers approximately 90% of the AFP spotting solutions can be identified. CONCLUSIONS: In this feasibility study we demonstrate that current methods for identifying initial BAC clones can be adapted to verify the identity of AFP spotting solutions used in printing arrays. Of these methods, AFP sequencing proves to be the most efficient for large scale identification of spotting solution in a high throughput manner.